The Management of Educational Marketing Strategies in Attracting Parental Interest at Al Hidayah Kindergarten in Pasuruan City - Mardiyah, Khusnul; Harris, Taufik; Wahyudi , M. Furqon (The Future of Education Journal, 2026)
This study aims to examine and describe the management of educational marketing strategies in increasing parents' interest at Al Hidayah Kindergarten in Pasuruan City. The high level of competition among early childhood education providers, especially in private kindergartens, requires administrators to implement appropriate and effective marketing strategies to attract parents’ attention. This research uses a qualitative approach with a descriptive design. The research informants are the administrators of Al Hidayah Kindergarten, with the focus of the study directed at the educational marketing strategies implemented by the institution. Data collection was carried out through in-depth interviews, observations, and document studies. The data analysis techniques include data reduction, data presentation, and conclusion drawing, with data validity tested using source and technique triangulation. The results show that the educational marketing strategy at Al Hidayah Kindergarten is carried out through the planning of flagship programs, setting affordable and flexible tuition fees, utilizing social media, interpersonal approaches to parents, and strengthening the school’s image by highlighting religious values and service quality. This strategy is considered effective in increasing parents’ interest and trust in the institution. The study is expected to provide practical contributions for early childhood education administrators in designing educational marketing strategies oriented toward community needs.